Information and communication technologies to address violence against women in emergency remote nursing teaching activities during the COVID-19 pandemic (Research, Society and Development, 2022)
Introduction: Violence against women is a multidimensional phenomenon that has increased significantly during the COVID-19 pandemic. Objective: To report the experience of developing a prevention, protection and support strategy for women at risk of violence, during the COVID-19 pandemic, mediated by the incorporation of Information and Communication Technologies and developed in undergraduate emergency remote teaching activities in nursing. Materials and Methods: experience report carried out in April 2020, with undergraduate nursing students who took a subject related to Women's Health, at a public university in the interior of the State of São Paulo, Brazil. The development of the strategy took place in five stages: 1) survey of available applications; 2) creation of a group in the WhatsApp application; 3) operationalization; 4) compilation of discussions and evaluation; 5) dissemination of the strategy. Results: A prevention, protection and support strategy was developed for women at risk of violence, during the COVID-19 pandemic, through content that was shared by message on WhatsApp® and, later, on the social networks Facebook®, Instagram® and Twitter®. Discussion: The development of the strategy was positively evaluated by the students on the occasion of the emergency remote teaching, emphasizing the importance of the internet and social networks as means to expand the discussions. Conclusion: The use of Information and Communication Technology as a strategy to break the invisibility and tackling violence against women during the COVID-19 pandemic was an innovative experience in an undergraduate course and demonstrates the importance of including them in teaching.